CFD modeling of waste cooking oil transesterification in a stirred tank reactor - Adeyemi, Nabeel A.; Mohiuddin, A. K. M.; Mohd Nor, Mohd Iskandr (IDOSI Publication, 2013)
In this paper, the numerical modeling of alkali-catalyzed waste cooking oil (WCO) transesterification in a 2-L stirred tank reactor (STR) is presented. Based on the Reynolds Average Navier-Stokes (RANS)equation, a 3-D model was developed to simulate the transesterification of WCO in a stirred tank reactor (STR)using a commercial numerical solver. Two models were compared for the reaction. One of the models included the rate constant (finite rate model) on one hand and the other (eddy dissipation model) helped account for turbulence. The turbulence parameter, turbulent kinetic energy and dissipation rate were obtained statistically from mean velocity data by PIV. The characteristic time scales were used to show the relevant mixing scale used to describe the process. Thermodynamic properties of the reaction components were incorporated as user defined function (UDF) for the mixing models in ANSYS Fluent. FAME yield were predicted in terms of species concentration and compared fairly well with experimental condition for 1 and 2-L STR, where yield from the numerical model varied by about 18 and 23 % for 1 and 2-L STR respectively.